1997
DOI: 10.1038/37151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of a volume-regulated chloride channel

Abstract: A volume-regulated chloride current (ICl.vol) is ubiquitously present in mammalian cells, and is required for the regulation of electrical activity, cell volume, intracellular pH, immunological responses, cell proliferation and differentiation. However, the molecule responsible for ICl.vol has yet to be determined. Although three putative chloride channel proteins expressed from cloned genes (P-glycoprotein, pICln and ClC-2 ) have been proposed to be the molecular equivalent of ICl.vol, neither P-glycoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
412
5
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(455 citation statements)
references
References 27 publications
36
412
5
1
Order By: Relevance
“…This P-gpassociated volume-regulated chloride channel is functionally blocked by P-gp-specific mAbs (42,43) and MDR1 antisense oligonucleotides (44). A molecular candidate for the volume-regulated chloride channel, ClC-3, has recently been identified, and was shown to be inhibited by the chloride channel-specific inhibitor 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid and the P-gp inhibitor tamoxifen (45). Since T cell activation depends in part on efficient cell-cell interactions during Ag recognition and costimulation, P-gp, through its associated chloride channel activity (46), may function as a regulator of cellular volume changes and cell shape adaptations during these processes.…”
Section: Discussionmentioning
confidence: 99%
“…This P-gpassociated volume-regulated chloride channel is functionally blocked by P-gp-specific mAbs (42,43) and MDR1 antisense oligonucleotides (44). A molecular candidate for the volume-regulated chloride channel, ClC-3, has recently been identified, and was shown to be inhibited by the chloride channel-specific inhibitor 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid and the P-gp inhibitor tamoxifen (45). Since T cell activation depends in part on efficient cell-cell interactions during Ag recognition and costimulation, P-gp, through its associated chloride channel activity (46), may function as a regulator of cellular volume changes and cell shape adaptations during these processes.…”
Section: Discussionmentioning
confidence: 99%
“…1 The roles of VSOR in cell volume regulation, proliferation, migration and cell death are well established, but its molecular identity has not fully been clarified until recently. 1,2 In the 1990s, several proteins, including P-glycoprotein, pI cln , and ClC-3, were proposed as molecular identities of VSOR, [3][4][5] but none of them has survived scrutiny. [6][7][8][9][10][11][12] In 2014, 2 research groups independently reported that the leucine-rich repeat containing 8A (LRRC8A), which has 4 transmembrane domains and a leucine-rich repeat (LRR) domain at the C-terminus, is a core factor of VSOR in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it would npg not be hard to imagine that AQP3 might also form molecular complexes with other ion channels to mediate sperm RVD. Such candidate molecules may involve the volume sensitive chloride channel CLC-3 [30] , which has been observed in mammalian sperm and has been implicated in sperm volume regulation [31,32] .…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 99%